Effects of serial and acute enteric-coated sodium bicarbonate supplementation on anaerobic performance, physiological profile, and metabolomics in healthy young men - Zhou, Nihong; Fan, Yongzhao; Kong, Xiaoyang; Wang, Xiangyu; Wang, Junde; Wu, Hao (Frontiers in Nutrition, 2022)
Background This study aimed to verify the effects of serial and acute enteric-coated sodium bicarbonate supplementation on anaerobic performance, physiological profile, and metabolomics in healthy young men. Methods Healthy young males (n = 12) ingested 0.2 g /kg body mass of enteric-coated sodium bicarbonate (ES) in serial enteric-coated sodium bicarbonate (SES) and acute enteric-coated sodium bicarbonate (AES) or a placebo (PL) in a randomized crossover design. After each supplement protocol, the subjects completed four Wingate anaerobic tests. Blood lactic acid (BLA), heart rate (HR), and ratings of perceived exertion (RPE) were measured in all conditions during the test, as was the subjective gastrointestinal–symptoms assessment questionnaire (GSAQ). Mean power (MP) and peak power (PP) were recorded after four WATs. Urine samples were collected before the test and 50 minutes after the 3rd WAT. Results Serial enteric-coated sodium bicarbonate supplementation improved anaerobic capacity in the third bout of WATs, as observed based on an increase in mean power (SES vs. PL (612.88±56.85 vs. 542.19±64.17 W), P = 0.025) and peak power (SES vs. PL (1071.30±149.07 vs. 905.11±149.90 W), P = 0.016). Acute ES supplementation did not affect anaerobic capacity. The occurrence of gastrointestinal symptoms after enteric-coated sodium bicarbonate supplementation was minimal in the current study. In particular, serial enteric-coated sodium bicarbonate supplementation had no gastrointestinal side effects before the test. AES tended to increase at the stage of BLA concentration increase than the other two groups, while SES and AES tended to decrease at the stage of BLA concentration decrease compared with the PL group. There was no significant difference in HR and RPE among the three groups. Based on targeted metabolomics analysis, the 50 min after the third WAT, the levels of lactate (P < 0.001), L-Malic acid (P < 0.05), and oxaloacetate (P < 0.05) were significantly higher in the SES group than in the PL group. Compared with the AES group, the levels of lactate and fumarate in the SES group were significantly increased (P < 0.05).